2017
DOI: 10.1159/000479083
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Comparing Ultrasound-Guided Transversus Abdominis Plane Block with Local Anesthetic Infiltration in Peritoneal Dialysis Catheter Implantation

Abstract: Background: The ultrasound-guided transversus abdominis plane (TAP) block has been demonstrated as a useful analgesia technique in lower-abdomen surgeries. We hypothesized that it could be the principal anesthesia technique for end-stage renal disease (ESRD) patients undergoing peritoneal dialysis (PD) catheter (PDC) implantation using the open dissection method. Methods: This was a single-center, prospective, randomized, and double-blinded study. All eligible patients were randomized into 2 groups: the TAP bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…1) should have been avoided. Li et al [12] reported superior analgesia and patient satisfaction with TAPB than with local anesthesia during the placement of a peritoneal dialysis catheter. It is possible that bilateral subcostal TAPB would have improved the quality of analgesia in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…1) should have been avoided. Li et al [12] reported superior analgesia and patient satisfaction with TAPB than with local anesthesia during the placement of a peritoneal dialysis catheter. It is possible that bilateral subcostal TAPB would have improved the quality of analgesia in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the methodological risk of bias assessment are presented in graphic and summary forms (Figures 2 and 3). In summary, 7 RCTs [10,15,17,20,[22][23][24] had a low risk of bias, and 8 RCTs [11-14, 16, 18, 19, 21] had an unclear risk of bias. The main reasons for the 8 RCTs having an unclear risk of bias were due to a failure to mention the following factors: randomization sequence generation, allocation concealment, blinding of participants and personnel, and blinding of outcome assessment.…”
Section: Risk Of Methodological Bias and The Quality Of Thementioning
confidence: 97%
“…In the subgroup analyses of nonlaparoscopic surgery, compared with WI, TAP block was associated with lower pain scores at rest at 2 h (MD = −0:69, 95% CI (-1.23, -0.16), I 2 = 4%), 6 h (MD = −0:79, 95% CI (-1.22, -0.36), I 2 = 0%), and 24 h (MD = −0:58, 95% CI (-0.90, -0.26), I 2 = 15%) but not at 1 h (MD = −0:32, 95% CI (-1.15, -0.52), I 2 = 64%), and in the subgroup analyses of laparoscopic surgery, compared with WI, TAP block was also associated with lower pain scores at rest at 2 h (MD = −0:94, 95% CI (-1.79, -0.08), I 2 = 2%), 6 h (MD = −0:89, 95% CI (-1.13, -0.65), I 2 = 0%), and 24 h (MD = −0:53, 95% CI (-0.75, -0.31), I 2 = 10%) but not at 1 h (MD = −0:30, 95% CI (-0.63, 0.03), I 2 = 44%) ( Fig S1 to Fig S4). Moreover, in the subgroup analyses of the surgical site in the upper abdomen, compared with WI, TAP block was associated with lower pain scores at rest at 2 h (MD = −0:94, 95% CI (-1.79, -0.08), I 2 = 2%), 12 h (MD = −0:74, 95% CI (-1.28, -0.20), I 2 = 1%), and 24 h (MD = −0:69, 95% CI (-1.00, -0.39), I 2 = 0%) but not 3 [12,17,23], no study reported postoperative pain scores during movement at 12 h, and five studies reported postoperative pain scores during movement at 24 h [14,15,17,23,24]. Compared with WI, TAP block was associated with lower pain scores during movement at 2 h (MD = −1:47, 95% CI (-2.32, 0.62), P = 0:0007), 4 h (MD = −0:65, 95% CI (-1.24, 0.06), P = 0:03), 6 h (MD = −0:73, 95% CI (-1.23, 0.24), P = 0:004), and 24 h (MD = −0:85, 95% CI (-1.16, 0.53), P < 0:00001) but not at 1 h (MD = −1:04, 95% CI (-2.07, 0.00), P = 0:05), and there were low levels of heterogeneity in five analyses (for 1 h: I 2 = 4%; for 2 h: I 2 = 0%; for 4 h: I 2 = 0%; for 6h: I 2 = 0%; and for 24h: I 2 = 0%) ( Figures 10-14).…”
Section: Postoperative Pain Scores Atmentioning
confidence: 99%
See 2 more Smart Citations